Methodology for high-accuracy infrared calibration in environments with through-wall heat flux - Michaud, M; Ornano, F; Chowdhury, N; Povey, T (Global Power and Propulsion Society, 2019)
This paper describes a new method for accurate in situ infrared (IR) calibration in environments with significant through-wall heat flux and surface temperature nonuniformity. In the context of turbine research environments, conventional approaches for in situ IR calibrations rely on thermocouples embedded in the surface or bonded to the surface using an adhesive layer. A review of the literature points to lack of emphasis on the uncertainty in the calibration arising from the effect of the adhesive substrate and paint on the temperature measured by the thermocouple, namely that under diabatic conditions (i.e. with through-wall heat flux) the measured temperature deviates from the true surface temperature. We present a systematic study of the sensitivity of the thermocouple temperature to installation conditions seen in typical laboratory IR calibration arrangements, and under realistic conditions of through-wall heat flux. A new technique is proposed that improves the calibration accuracy by reducing the difference between the thermocouple measurement and the external wall temperature seen by the infrared camera. The new technique has the additional advantage of reducing the uncertainty associated with selecting an appropriate pixel in the IR image, by providing a region with greater temperature uniformity especially in environments with significant underlying lateral surface temperature variation. The new approach is experimentally demonstrated and compared to more conventional measurement techniques on a heavily film-cooled nozzle guide vane assembly operated at highly engine-representative conditions. The proposed technique is demonstrated to significantly improve the measurement accuracy for IR in situ calibrations in environment with through-wall heat flux and surface temperature non-uniformity.